Breast mass imaging identification of rare pleomorphic adenoma after follow-up of gastric cancer surgery: a case report - He, XianJun; Lu, LiLing (Frontiers in Oncology, 2026)
This study explores the imaging diagnosis and differential diagnosis of pleomorphic adenoma (PA) of the breast. PA is a rare benign tumor of the breast with a risk of recurrence, though it rarely undergoes malignant transformation. Therefore, extensive local excision is often performed, and a correct preoperative diagnosis of this lesion is important to ensure appropriate surgical treatment. Due to its rarity and nonspecific imaging findings, preoperative diagnosis is challenging and prone to misdiagnosis, especially in patients with a history of other malignancies. We present the case of a patient with a history of gastric cancer (GC) who presented with a breast mass that was pathologically confirmed to be PA. We analyzed the tumor’s imaging and pathological characteristics and discussed the diagnostic strategy.